Analysis of Financial Administration Management at the Murhum District Office, Baubau City - Uli, Nur Zarliani; Agustyawati, Dwi; Indrawati, Indrawati; Febriyanti, Febriyanti (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study investigates the financial administration practices at the Murhum District Office, Baubau City, using a qualitative descriptive approach aimed at understanding the implementation of regional financial governance in line with national regulations. The research involved a total of 20 staff members, with purposive sampling of three employees directly involved in financial administration. In addition, financial documents from the years 2020 to 2022 were analyzed to complement the primary data. Data collection methods included direct observation of financial procedures, in-depth interviews with selected financial staff, and document analysis to validate the implementation process. The findings show that the financial administration at the Murhum District Office is carried out in accordance with Minister of Home Affairs Regulation No. 13 of 2006 and its amendment No. 59 of 2007, which outline the principles and procedures of regional financial management. The administrative process covers key components such as financial planning, budgeting, execution, monitoring, and accountability. Notably, the budgeting process reflects a balanced alignment between projected revenues and expenditures, demonstrating efficient financial planning. The study also emphasizes that the financial activities are consistent with the objectives of Law No. 32 of 2004 concerning Regional Government, particularly regarding the transparent and accountable use of the Regional Income and Expenditure Budget (APBK). Overall, the research concludes that the financial administration system in the Murhum District Office is well-organized, legally compliant, and contributes positively to the realization of good governance practices at the local level